2016
DOI: 10.3748/wjg.v22.i18.4576
|View full text |Cite
|
Sign up to set email alerts
|

Correlation betweenHelicobacter pylori-associated gastric diseases and colorectal neoplasia

Abstract: H. pylori infection as well as H. pylori-associated gastric diseases are risk factors for colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“… 11 , 27 Higher risk of colorectal neoplasia in patients with H. pylori infections is also reported. 28 The unfavorable influences of H. pylori include a short stature and IDA, 29 although these were not evident in our study. However, H. pylori infection does not always have negative consequences, and some effects may be beneficial.…”
Section: Discussioncontrasting
confidence: 64%
“… 11 , 27 Higher risk of colorectal neoplasia in patients with H. pylori infections is also reported. 28 The unfavorable influences of H. pylori include a short stature and IDA, 29 although these were not evident in our study. However, H. pylori infection does not always have negative consequences, and some effects may be beneficial.…”
Section: Discussioncontrasting
confidence: 64%
“…A large population based case-control study that enrolled 156000 individuals showed a positive association between IM and colorectal adenomas (adjusted OR = 1.24, 95%CI: 1.17-1.32), but without including an analysis of the relationship between H. pylori -related IM and colorectal adenomas[ 9 ]. Furthermore, a recent study showed that individuals with IM were more likely to have adenomas with high-grade intraepithelial lesions (OR = 3.218, 95%CI: 0.767-13.509)[ 20 ]. To our knowledge, no study has analyzed the relationship between H. pylori -related IM and colorectal neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of case-control studies ( n = 22) were conducted in Asia, an area with a high burden of H . pylori infection [6, 7, 11, 18, 2426, 2833, 35, 3942, 44, 46, 50, 51]. Screening programs for gastric cancer in certain Asian countries include esophagogastroduodenoscopy on a regular basis, which allows assessing H .…”
Section: Epidemiological Findingsmentioning
confidence: 99%
“…Independent of the method applied, however, the majority of case-control studies ( n = 30) reported a positive association of H . pylori with colorectal adenoma and/or cancer prevalence, with odds ratios varying between 1.15 and 10.6 [6, 7, 9, 11, 12, 1618, 2135, 3740, 42, 46, 51]. A meta-analysis by Wu and colleagues (2013) reported a summary estimate of 1.66 (95% confidence interval: 1.30–1.97) for colorectal adenoma and 1.39 (95% confidence interval: 1.18–1.64) for CRC [52], which reflects reported results from the majority of case-control studies cited in this review.…”
Section: Epidemiological Findingsmentioning
confidence: 99%
See 1 more Smart Citation